2018
DOI: 10.1038/nature25979
|View full text |Cite
|
Sign up to set email alerts
|

Extensive impact of non-antibiotic drugs on human gut bacteria

Abstract: A few commonly used non-antibiotic drugs have recently been associated with changes in gut microbiome composition, but the extent of this phenomenon is unknown. We screened >1000 marketed drugs against 40 representative gut bacterial strains, and found that 24% of the drugs with human targets, including members of all therapeutic classes, inhibited the growth of at least one strain. Particular classes such as the chemically diverse antipsychotics were overrepresented. The effects of human-targeted drugs on gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,323
7
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,521 publications
(1,397 citation statements)
references
References 64 publications
50
1,323
7
17
Order By: Relevance
“…Enterococcus and some anaerobic bacteria such as Clostridium difficile and Clostridium perfringens [3,[120][121][122]. Similarly, Gram-negative bacteria such as Citrobacter spp, Pseudomonas aeruginosa, Klebsiella pneumoniae and Morganella morganii have been proven to be susceptible to SSRIs [120,123].…”
Section: Gut Microbiota and Serotonin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococcus and some anaerobic bacteria such as Clostridium difficile and Clostridium perfringens [3,[120][121][122]. Similarly, Gram-negative bacteria such as Citrobacter spp, Pseudomonas aeruginosa, Klebsiella pneumoniae and Morganella morganii have been proven to be susceptible to SSRIs [120,123].…”
Section: Gut Microbiota and Serotonin Productionmentioning
confidence: 99%
“…These gut bacteria has coevolved with the human body to perform numerous beneficial functions ranging from being simple fermenters of food to having profound effects on the host immune development, metabolism and food preferences, brain development, stress responses, pain and behavior [1][2][3][4][5]. Consequently, disruptions or alterations in this resilient relationship is a significant factor in many diseases such as inflammatory gastrointestinal diseases, and neuropsychiatric disorders, including depression [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The final version may differ from this version. representative gut bacterial strains and demonstrated that many of them inhibited bacterial growth in vitro (Maier et al, 2018); however, it was not determined whether metabolism took place. Such systematic screening methodologies coupled with analytical techniques for drug quantification and speciation will help uncover additional interactions between drugs and the gut microbiome.…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%
“…Furthermore, care needs to be taken to sync the growth phase of control and drug exposed cultures to avoid false positives due to changes in cellular physiology. Finally, many non-antibiotic drugs can have bacteriostatic or even bacteriocidal effects during in vitro growth (Maier et al, 2018) 11 the translation of these results. Recently, by screening a collection of 25 Coriobacteriia strains and using our ElenMatchR tool for comparative genomics , we were independently able to identify a single genomic loci conserved in all strains capable of digoxin metabolism (Koppel et al, 2018).…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%
“…Recently, Maier et al [70] showed that a large amount of non-antibiotic human-targeted drugs have antimicrobial properties. Among them, drugs that can be prescribed during pregnancy, such as proton pump inhibitors, were found to disturb the growth of commensal bacteria (Table 2).…”
Section: External Challenges To Maternal Microbiota Dynamicsmentioning
confidence: 99%